Così lontane, così vicine. Famiglie migranti, ruoli familiari e nuove configurazioni di genitorialità - Francesca Crivellaro (Archivio Antropologico Mediterraneo)
Research has acknowledged the family as a useful conceptual entity to analyse the migration experience of women and men whose life cycle and reproductive choices span between different cultural contexts. Migrant families’ practices are often constructed in public discourse as a threat to the social cohesion of the receiving countries, as they are deemed incompatible with “Western modernity”. Drawing on ethnographic research carried out in Ravenna (Italy), the paper addresses the issue of evolving gender and care roles in migrant families. By specifically focusing on the ways in which migrant fathers and mothers renegotiate norms, visions and practices related to children’s care within a broader reconfiguration process of the representations underpinning couple and parenting relationships, the contribution aims to shed light on the dynamic nature of family roles.